Capital Account Convertibility and Risk Management in India - Sy, Amadou (Washington, D.C. : International Monetary Fund, 2007)
This paper takes a closer look at the prudential and regulatory measures needed to prepare India's financial system to manage the risks arising from fuller capital account convertibility (FCAC). The paper contributes to the debate on FCAC in two ways. First, it reviews the potential and existing financial stability challenges to FCAC in India. Second it studies how prudential regulation and supervision is addressing these challenges. The main conclusion is that regulatory and supervisory measures alone are not enough and will need to be complemented by improvements in Indian banks' risk management and further development of the domestic capital markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet